PENGARUH GOOD CORPORATE GOVERNANCE, CAPITAL ADEQUACY RATIO DAN NON PERFORMING FINANCING TERHADAP KINERJA KEUANGAN PADA BANK SYARIAH MANDIRI - M.Si, Drs. Supriadi, (eBA Journal: Journal Economics, Bussines and Accounting, 2015)
One of policies that used by banks in indonesia especially bank syariah to control and direction of financial performance is to carry out good corporate governance , monitor capital adequacy ratio and non performing financing every year in the form of financial reports and reports on the implementation of good corporate governance. This research compiled to know the influence of good corporate governance, capital adequacy ratio and non performing financing against financial performance on the tire of syariah mandiri .Data analysis stage using methods linear regression double spss series program for windows version 20.0 . From an analysis of data known that the variable good corporate governance (x1), capital adequacy ratio (x2) and non performing financing (x3) in together have no influence that significantly to financial performance on a bank syariah mandiri, with indicated by f-hitung 0,065 larger than 0.05. As for the value of the coefficients determined worship of idols ( R2 ) as much as 0,80. This means 80,7 % financial performance on a bank syariah mandiri affected by the application of good corporate governance, capital adequacy ratio and non performing financing, while 19.3 % influenced by various other factors.The result of a partial correlation in which (t-test) known that the variable good corporate governance (x1) having significant influence on the performance of financial on a bank syariah mandiri, is as much as -2,573 with sigifikansi 0,018. Variable while capital adequacy ratio (x2) not having an influence that was significantly by 0,087 with significance 0,443 economic situation and variable non performing financing (x3) not having the effect on financial performance on a bank syariah mandiri as much as -0,341 with significance 0,159. Besides, variable most dominant of its effect on financial performance against on a bank syariah mandiri was good corporate governance. Writer suggested researchers next to add other variables for example variable ROE, LDR, BOPO, NIM and others to the research results more accurate. Said the key: good corporate governance, capital adequacy ratio, non performing financing, return on assets, bank syariah mandiri .